2023
DOI: 10.31616/asj.2022.0015
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Skeletal Features of Developmental Cervical and Lumbar Spinal Stenosis

Abstract: Study Design: Cross-sectional study.Purpose: To report the prevalence and relationship of developmental cervical and lumbar spinal stenosis (DCSS and DLSS) with the bone parameters of the skull and extremities.Overview of Literature: DCSS and DLSS are found occasionally in daily practice. DCSS and DLSS can cause compressive myelopathy, radiculopathy, and cauda equina syndrome; however, data on their prevalence and correlation with skull and skeletal extremity profiles is scarce.Methods: A cross-sectional measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…19 The selection of incorrect lumbar spine levels increases the likelihood of identifying the wrong lumbar nerve root, which can result in the treatment of incorrect lumbar segment levels during interventional or surgical procedures. 20 Historically, several methods for accurately identifying the lumbar spine level have been reported, including a method using the 12th rib, iliolumbar ligament, kidney level, and craniocaudal level on whole-spine radiographs. However, conventional methods are not accurate; [21][22][23] spine physicians have therefore endeavored to develop further methods for accurately identifying lumbar spine segment numbers.…”
Section: Discussionmentioning
confidence: 99%
“…19 The selection of incorrect lumbar spine levels increases the likelihood of identifying the wrong lumbar nerve root, which can result in the treatment of incorrect lumbar segment levels during interventional or surgical procedures. 20 Historically, several methods for accurately identifying the lumbar spine level have been reported, including a method using the 12th rib, iliolumbar ligament, kidney level, and craniocaudal level on whole-spine radiographs. However, conventional methods are not accurate; [21][22][23] spine physicians have therefore endeavored to develop further methods for accurately identifying lumbar spine segment numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate determination of the lumbar spine segment is of great importance [18]. Lumbar spine pathology and related clinical symptoms are signi cantly associated with speci c lumbar nerve roots, which can be localized to the lumbar spine level [19]. Thus, selecting improper lumbar spine levels makes identifying the wrong lumbar nerve root likely, resulting in the management of improper lumbar segment levels during interventional or surgical procedures [20].…”
Section: Discussionmentioning
confidence: 99%
“…We were intrigued by the article by Kasai et al [ 1 ], which found that a small skull, small transverse diameter of the foramen magnum, and the small orbital bone were significantly correlated with developmental cervical spinal stenosis (DCSS). However, we have some concerns about this paper.…”
mentioning
confidence: 99%